Fijación larval y crecimiento del mejillón Mytella guayanensis L. (Bivalvia: Mytilidae) en Isla Chira, Costa Rica - Sibaja, Wilberg G. (Revista de Biología Tropical, 1988)
Collectors of wood, P.V.C., glassfiber, rope and tiles were tested in an estuary. Larvae attached more frequently to tile, but Chtalanus crustaceans were more abundant on this substratum and reduced the growth of M. guayanensis (August-January). 1.893 larva e were collected. Nylon collectors produced 128.393 larvae (February-July). Most larvae were collected from February to July, with a peak between April and May (end of dry season and early wet season).